2006
DOI: 10.1097/00001665-200603000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Intracranial Volume and the Surface Area of the Foramen Magnum

Abstract: Several investigators have estimated the intracranial volume (ICV) in the past which indirectly reflects the brain volume. Most of these studies have been made on the dry skulls using linear dimensions, packing methods or occasionally radiological methods. It is also reported that the etiology of cerebellar tonsillar herniation is closely related to the size of the foramen magnum (FM). In the present study the ICVs have been estimated in 28 dry skulls using filling water method and the surface area of FMs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
18
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 5 publications
6
18
0
6
Order By: Relevance
“…However, Golalipoor et al (2005) have reported skull volume to be 1420.60± 85 cm 3 in males and 1227.2±120 cm 3 in Turkmen race of Gorgan, which is closer to our study compared to the mentioned Indian study. Acer et al (2006) calculated the internal skull volume to be 1311±133 cm 3 which is close to amount achieved in the present study (1276.94±310 cm 3 ). In regression analysis of our study, we found that age and BMI in young males and females is positively correlated with brain volume which supports the results of Gustafson's study (Gustafson et al, 2004).…”
Section: Discussionsupporting
confidence: 89%
“…However, Golalipoor et al (2005) have reported skull volume to be 1420.60± 85 cm 3 in males and 1227.2±120 cm 3 in Turkmen race of Gorgan, which is closer to our study compared to the mentioned Indian study. Acer et al (2006) calculated the internal skull volume to be 1311±133 cm 3 which is close to amount achieved in the present study (1276.94±310 cm 3 ). In regression analysis of our study, we found that age and BMI in young males and females is positively correlated with brain volume which supports the results of Gustafson's study (Gustafson et al, 2004).…”
Section: Discussionsupporting
confidence: 89%
“…The underlying reason is that these measurements provide clear images of skeletal features in cases where flesh is present (19,20). Two-dimensional imaging methods including antero-posterior and lateral cephalometric radiographs have been generally used in previous studies for skull measurements (18). The use of three-dimensional radiographic images like medical computed tomography (CT) has become more common in recent years (6,(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the investigators have estimated the CC in the past which indirectly reflects the brain volume (Gault et al, 1988;Wolf et al, 2003;Mazonakis et al, 2004). One of the most satisfactory method for measuring CC of a dry skull is measuring the amount of water poured into a balloon which introduced into the cranial cavity through the foramen magnum (Manjunath, 2002a;Acer et al, 2006). Most of those available studies have been made on dry skulls using linear dimensions, packing methods or occasionally radiological methods.…”
Section: Introductionmentioning
confidence: 99%